Take-up of joint and individual liability loans: an analysis with laboratory experiment - Susmita Baulia (Elsevier, 2022)
This paper reports a study on decision-making by borrowers regarding take-up of different loan types in a laboratory microfinance experiment. I show that when prospective borrowers are offered a flexible choice of different loan types (here, individual liability (IL) and joint liability (JL)), take-up increases. This is due to heterogeneous borrowers self-selecting into different loan types. Results suggest that more risk averse borrowers are less willing to take up IL loan and less selfish borrowers show signs of higher inclination to take up JL loan. The results collectively imply that microloan offers need to be customized according to the heterogeneous preferences of borrowers; also, there needs to be enough flexibility in the offered choice-set for better self-selection. This would result in a substantial increase in the take-up rate of microloans by the borrowers.